2009
DOI: 10.1128/aac.01568-08
|View full text |Cite
|
Sign up to set email alerts
|

Trypanothione Reductase High-Throughput Screening Campaign Identifies Novel Classes of Inhibitors with Antiparasitic Activity

Abstract: High-throughput screening of 100,000 lead-like compounds led to the identification of nine novel chemical classes of trypanothione reductase (TR) inhibitors worthy of further investigation. Hits from five of these chemical classes have been developed further through different combinations of preliminary structure-activity relationship rate probing and assessment of antiparasitic activity, cytotoxicity, and chemical and in vitro metabolic properties. This has led to the identification of novel TR inhibitor chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
60
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 55 publications
1
60
0
Order By: Relevance
“…We have previously reported on a high-throughput screening campaign conducted to identify inhibitors of trypanothione reductase (TR) that might consequently be toxic to trypanosomatids. 4,5 Amongst the identified hits was a benzhydryl tropinone oxime that was found to be potently toxic towards T. cruzi with an EC 50 of 110 nM and highly selective for this organism relative to other trypanosomatids such as Leishmania donovani and Trypanosoma brucei. 5 These data are summarized in Figure 2.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported on a high-throughput screening campaign conducted to identify inhibitors of trypanothione reductase (TR) that might consequently be toxic to trypanosomatids. 4,5 Amongst the identified hits was a benzhydryl tropinone oxime that was found to be potently toxic towards T. cruzi with an EC 50 of 110 nM and highly selective for this organism relative to other trypanosomatids such as Leishmania donovani and Trypanosoma brucei. 5 These data are summarized in Figure 2.…”
mentioning
confidence: 99%
“…4,5 Amongst the identified hits was a benzhydryl tropinone oxime that was found to be potently toxic towards T. cruzi with an EC 50 of 110 nM and highly selective for this organism relative to other trypanosomatids such as Leishmania donovani and Trypanosoma brucei. 5 These data are summarized in Figure 2. For several reasons, significantly amongst these being the very weak trypanothione reductase inhibitory activity of compound 1 (EC 50 35uM, Figure 2), we have previously argued that the observed potent T.cruzi-selective trypanocidal activity could likely be due to off-target activity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Different chemotypes were identified that showed selectivity for TR over human glutathione reductase (15). Another approach revealed compounds with potent antiparasitic activity, but only moderate correlation with TR inhibition (6). All enzymes establishing the parasite peroxidase system, namely TR, Tpx, and both types of tryparedoxin peroxidases, have been shown to be essential for T. brucei (16 -19) and thus fulfill a crucial prerequisite of a putative drug target molecule.…”
mentioning
confidence: 99%
“…The dithiol is kept reduced by NADPH and the flavoenzyme trypanothione reductase (TR), the system replacing the glutathione/glutathione reductase couple of the mammalian host (4). TR is the most thoroughly studied enzyme of the trypanothione metabolism, and a large number of inhibitors has been identified (5)(6)(7)(8)(9). Tpx is a distant member of the thioredoxin (Trx) protein family.…”
mentioning
confidence: 99%